Pengaruh Harga, Kualitas Produk, dan Gaya Hidup terhadap Proses Keputusan Pembelian Produk Hijab di Nadiraa Hijab Yogyakarta - Anita Rachmawati; Any Agus Kana; Yunita Anggarini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
The development of Muslim fashion is currently so fast, many Muslim fashion trends are currently developing, one of which is the hijab trend. Because nowadays the hijab is no longer about religion but has started to become a part of everyday life or to support one's appearance. The number of models with different qualities, varying prices, and also the usefulness of these hijab models make the hijab even more in demand. The purpose of this study was to examine the factors that influence consumer decisions to buy hijab products at Nadiraa Hijab, including price, product quality, and lifestyle. This research is quantitative survey research, by distributing questionnaires to respondents who are buyers of Nadiraa Hijab products. The sample size is 170 respondents who are determined by the non-probability-purposive sampling technique. By using multiple linear analysis, it is found that consumers' decisions to buy hijab products are influenced by price and consumer lifestyle variables, and are not influenced by product quality. Another finding shows that 47.4% of the purchasing decision variable can be explained by the independent variable, namely the variable price, product quality, and lifestyle, and the rest is influenced by other variables outside the research.